1970
DOI: 10.1042/bj1190165
|View full text |Cite
|
Sign up to set email alerts
|

Homologies in amino acid composition and structure of histone F2al isolated from human leukaemic cells

Abstract: Histones F2al extracted from normal and neoplastic cells possess similar amino acid compositions. Tryptic and chymotryptic peptides of the F2al histones have identical chromato-electrophoretic R(F) values. It is concluded that histones F2al from various sources have similar overall structures. The observed differences in the ratios of in-N-monomethyl- and di-in-N-methyl-lysine in the histones from normal and neoplastic cells may be of significance with respect to gene regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1975
1975
1993
1993

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…There are also differences in aggregation in Ca(Cl0 4 ). 2 The conformation of the backbone of PLL is significantly affected by changes at the extremity of the side chain which do not change the charge. Although these results have been obtained so far with extensively methylated PLL, they suggest that methylation of proteins at one or a few sites may have local effects on conformation, dynamics, and on hydrophobic and electrostatic interactions involved in intramolecular and intermolecular interactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also differences in aggregation in Ca(Cl0 4 ). 2 The conformation of the backbone of PLL is significantly affected by changes at the extremity of the side chain which do not change the charge. Although these results have been obtained so far with extensively methylated PLL, they suggest that methylation of proteins at one or a few sites may have local effects on conformation, dynamics, and on hydrophobic and electrostatic interactions involved in intramolecular and intermolecular interactions.…”
Section: Resultsmentioning
confidence: 99%
“…There have been a number of findings on methylated proteins which have stimulated speculations about the functions affected by methylation. It has been reported that histones of malignant cells and rapidly multiplying cells have a lower ratio of dimethyllysine to monomethyllysine (2,3). Das and Kanungo found that methylation of histones is highest in old rats, while methylation of non-histone chromosomal proteins is highest in young rats (4).…”
mentioning
confidence: 99%
“…The rate of phosphorylation of histone Hi has been shown to be correlated with the growth rate of several tumors (Balhorn et al, 1972). Concerning the eventual structural changes, they have been investigated only in histone H4 from human leukemic cells (Desai and Foley, 1970), rat Novikoff hepatoma (Wilson et al, 1970), rat chloroleukemia (Sautiére et al, 1971), and benzopyrene-induced tumor (A. Martinage, personal communication). No differences have been found between histone H4 from tumoral source and calf-thymus histone H4.…”
mentioning
confidence: 99%